2019
DOI: 10.1109/access.2019.2947196
|View full text |Cite
|
Sign up to set email alerts
|

A Correction Model for the Continuous Deflection Measurement of Pavements Under Dynamic Loads

Abstract: Pavement deflection is the primary indicator reflecting road-bearing capacity. The falling weight deflectometer (FWD) and the Benkelman beam deflectometer (BBD) are widely used in deflection measurement, and are suitable for measuring the elastic deflection of pavement under static loading or dynamic impact loading. In recent years, there has been an increasing interest in continuous dynamic deflectometers, especially velocity-based deflectometers. The velocity-based continuous dynamic deflectometers, such as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Wix et al [16] compared the TSD measurements in New South Wales in two years and found better repeatability of the maximum deflection. Liao et al [1] showed that the variability of TSD measurements at three speeds (30,50, and 80 km/h) was lower than 5%. Shrestha et al [17] discussed the repeatability and correlation of TSD using approximately 9540 km of measuring data.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wix et al [16] compared the TSD measurements in New South Wales in two years and found better repeatability of the maximum deflection. Liao et al [1] showed that the variability of TSD measurements at three speeds (30,50, and 80 km/h) was lower than 5%. Shrestha et al [17] discussed the repeatability and correlation of TSD using approximately 9540 km of measuring data.…”
Section: Introductionmentioning
confidence: 99%
“…Deflection is a significant property reflecting the bearing capacity of the pavement [1]. Earlier, instruments such as the Benkelman Beam Deflectometer (BBD) and the Falling Weight Deflectometer (FWD) were used to measure it.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In field tests, there are three typical methods of deflection measurement: static load-based deflectometer, which provides the maximum deflection under a static load 14 ; stationary dynamic impact deflection measurement, as the falling weight deflectometer (FWD) 15 ; and moving dynamic deflection measurement, e.g. the laser dynamic deflectometer (LDD), which captures the deflection along a line on the pavement as the vehicule moves 16 , 17 . Though the static load-based Benkelman beam has been used extensively in India and several other countries for structural evaluation of in-service pavements, the FWD is considered to be the most appropriate equipment 14 , 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Under different load levels, 19 kinds of structures' deflection basins with different stiffness levels have been regularly tested and data collected, and their changes have been analysed [14]. As an important indicator reflecting the bearing capacity of asphalt pavement structures, deflection has always been the focus of highway builders and scientific researcher [15][16][17]. This paper uses the data collected from the RIOHTRACK ring road to predict the deflection basin of the road by establishing a multi-level neural network model.…”
Section: Introductionmentioning
confidence: 99%